Answers

  • Brainly User
2015-09-15T02:41:05+08:00
If you're looking for the product, multiply the 3 binomials which yields
x³ + 4x² + x - 6

The solution to this polynomial function:
P(x) = (x+3) (x-1)(x+2)
0 = (x+3) (x-1) (x+2)
x+3=0
x = -3

x-1 = 0
x = 1

x + 2 = 0
x = -2

The zeros of the polynomial: -3, 1, -2
0
alam mo naman po pal ehh
hmm, yes. but i couldn't post the correct answer because the two boxes have been filled-out. Unless a moderator finds out that answers do not satisfy the question and deletes incorrect answers, then others who could provide correct answers with accompanying solution would not have the opportunity to help. More importantly, the inquirer will not get the correct answer to his homework :-) Keep helping others, you're a smart kid :-)